Habituation of Salmonella spp. at Reduced Water Activity and Its Effect on Heat Tolerance - Mattick, K. L. (American Society for Microbiology, 2000)
The effect of habituation at reduced water activity (a(w)) on heat tolerance of Salmonella spp. was investigated. Stationary-phase cells were exposed to a(w) 0.95 in broths containing glucose-fructose, sodium chloride, or glycerol at 21°C for up to a week prior to heat challenge at 54°C. In addition, the effects of different a(w)s and heat challenge temperatures were investigated. Habituation at a(w) 0.95 resulted in increased heat tolerance at 54°C with all solutes tested. The extent of the increase and the optimal habituation time depended on the solute used. Exposure to broths containing glucose-fructose (a(w) 0.95) for 12 h resulted in maximal heat tolerance, with more than a fourfold increase in D(54) values. Cells held for more than 72 h in these conditions, however, became as heat sensitive as nonhabituated populations. Habituation in the presence of sodium chloride or glycerol gave rise to less pronounced but still significant increases in heat tolerance at 54°C, and a shorter incubation time was required to maximize tolerance. The increase in heat tolerance following habituation in broths containing glucose-fructose (a(w) 0.95) was RpoS independent. The presence of chloramphenicol or rifampin during habituation and inactivation did not affect the extent of heat tolerance achieved, suggesting that de novo protein synthesis was probably not necessary. These data highlight the importance of cell prehistory prior to heat inactivation and may have implications for food manufacturers using low-a(w) ingredients.